Prevalence and correlates of non-fatal overdose among people who use drugs: findings from rapid assessments in Massachusetts, 2017-2019 - Shikhar Shrestha; Thomas J. Stopka; Jaclyn M. W. Hughto; Patricia Case; Wilson R. Palacios; Brittni Reilly; Traci C. Green (BMC, 2021)
Abstract Background People who experience non-fatal overdose (NFOD) are at high risk of subsequent overdose. With unprecedented increases in fentanyl in the US drug supply, many Massachusetts (MA) communities have seen a surge in opioid-related overdoses. The objective of this study was to determine factors associated with lifetime and past year NFOD in at-risk MA communities. Methods We conducted multiple rapid assessments among people who use drugs (PWUD) in eight MA communities using non-probability sampling (purposive, chain referral, respondent-driven) methods. We collected sociodemographic, substance use, overdose history, substance use treatment, and harm reduction services utilization data. We examined the prevalence of NFOD (lifetime and past year) and identified factors associated with NFOD through multivariable logistic regression analyses in a subset of 469 study participants between 2017 and 2019. Results The prevalence of lifetime and last year non-fatal opioid overdose was 62.5% and 36.9%, respectively. Many of the study participants reported heroin (64%) and fentanyl (45%) use during the 30 days preceding the survey. Nonprescription buprenorphine and fentanyl use were independently associated with higher odds of lifetime NFOD, while marijuana use was associated with lower odds of lifetime NFOD (p < 0.05). Injection as the route of administration, benzodiazepine, nonprescription buprenorphine, heroin, and fentanyl use were independently associated with higher odds, while methadone use was associated with lower odds of past year NFOD (p < 0.05). Conclusion We documented a high prevalence of past year and lifetime NFOD among PWUD in MA. Our findings provide indicators that can help inform interventions to prevent overdoses among PWUD, including overdose prevention, medication treatment, and naloxone distribution.